2013
DOI: 10.1017/s0022050713000326
|View full text |Cite
|
Sign up to set email alerts
|

Competing Bimetallic Ratios: Amsterdam, London, and Bullion Arbitrage in Mid-Eighteenth Century

Abstract:  PILAR NOGUES-MARCOThis article analyzes the stability of bimetallism for countries operating in integrated bullion markets that enact different legal ratios. I articulate a new theoretical framework to demonstrate that two countries can both be bimetallic only if they coordinate their legal ratios. The theoretical framework is applied to the mid-eighteenth century when London's legal ratio was 3.8 percent higher than that of Amsterdam. I find that Amsterdam was effectively on the bimetallic standard, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although the transaction cost of arbitrage exhibits a downward trend between the sixteenth (4 per cent) and nineteenth centuries (0.5 per cent), the transaction cost of arbitrage estimated in this article is relatively low compared to that available in the existing literature (Nogues-Marco 2013, pp. 21–3; Li 2015, p. 1219; Bignon et al 2017, pp.…”
Section: IVmentioning
confidence: 55%
See 1 more Smart Citation
“…Although the transaction cost of arbitrage exhibits a downward trend between the sixteenth (4 per cent) and nineteenth centuries (0.5 per cent), the transaction cost of arbitrage estimated in this article is relatively low compared to that available in the existing literature (Nogues-Marco 2013, pp. 21–3; Li 2015, p. 1219; Bignon et al 2017, pp.…”
Section: IVmentioning
confidence: 55%
“…Well-integrated and efficient financial markets promote resource allocation and facilitate economic development. The integration of European financial markets in the eighteenth and nineteenth centuries has been quantitatively analysed, establishing that European financial markets were already highly integrated and efficient in exploiting arbitrage opportunities (Schubert 1989; Neal 1990; Flandreau et al 2009a; Nogues-Marco 2013; Bignon et al 2017). Since the seventeenth century, bills of exchange were commonly discounted and assigned to a third party with endorsement.…”
mentioning
confidence: 99%
“…Comparison with bimetallic arbitrage of later ‘metallist’ periods (e.g. Friedman 1990; Nogues-Marco 2013) reveals key incentives for trading arising from the presence of sufficient difference across locations between the fixed legal exchange rate for gold and silver coinage and the variable market agio for exchanging bullion. Absent merchant mint access combined with a ‘caged’ monetary system, such bimetallic arbitrages were not possible.…”
Section: VIImentioning
confidence: 99%
“…It is commonly believed that Sir Isaac Newton, Master of the Mint, mistakenly overvalued gold at the Mint in 1717. 4 However, Nogues-Marco (2013) demonstrated that the London bimetallic ratio remained too high not because of Newton's 'mistake', but because Parliament did not alter the monetary standard of England, as Newton proposed, to adjust the legal ratio to the European market ratio. Parliament decided 'that no Alteration be made in the Standard of the Gold and Silver Coins of this Kingdom, in Fineness, Weight or Denomination'.…”
Section: Introductionmentioning
confidence: 99%